Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
ISBN 978-91-85735-17-4
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Sex, Food and Female Power: Discussion of Data Material from Northern Mozambique - Arnfred, Signe (Sexualities, 2007)
Issues of sex and food are often inscribed in male/female relationships. Frequently in a western context sex is perceived as a site of male power and female subordination, while food and cooking are seen as female domains, but still sites of subordination, as elements of women's household chores. In this article, looking at issues of sex and food in a rural matrilineal setting, power aspects of male/female relationships as mediated through sex and food emerge somewhat differently. Sexual proficiency is here a woman's art, mastered by old women and transmitted to the young. Also, in a setting where daily life is largely based on subsistence production, food and cooking become domains of power, again with old women in control. Based on fieldwork in northern Mozambique and with reference to African feminist conceptualizations of male/female power relationships, the article makes a case for rurality and ‘tradition’ not necessarily being adverse to female power in social relationships.
Publisher: SAGE Publications Ltd
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; gender / género; youth / juventude